Systematic Literature Review: Gamification for Promoting Healthy Food Purchases - Elfindah Princes (APPS Publications, 2023)
Purposes - This systematic literature review explores the application of Gamification in promoting healthy food purchases within the context of digital marketing. The purpose of this review is to investigate how Gamification strategies, such as points, badges, leaderboards, and rewards, have been utilized to influence consumer behavior, particularly encouraging healthier dietary choices. Methodology - The methodology follows PRISMA guidelines, involving a comprehensive search of relevant studies published between 2010 and 2023. A total of 35 peer-reviewed articles were analyzed to identify key themes, mechanisms, and outcomes associated with Gamification in digital marketing and health promotion. Findings - The findings suggest that Gamification effectively increases consumer engagement and promotes healthy food purchases by using a combination of behavioral, reward, and social mechanisms. Novelty - The novelty of this review lies in its focus on the intersection of Gamification and health promotion, particularly in the underexplored area of encouraging healthy food consumption. Conclusion - The conclusion emphasizes that Gamification has the potential to be a powerful tool for behavior change in the digital marketing of healthy foods. However, further research is needed to explore the long-term effects of these strategies. Research Implications - The research implications highlight the importance of integrating Gamification elements into health-focused marketing campaigns to improve consumer engagement and foster sustained behavior change. Digital marketers and health practitioners can leverage these findings to design more effective interventions promoting healthier dietary habits.